Miejsce metody porównawczej w teorii rewolucji Thedy Skocpol. Próba eksplikacji w aparaturze pojęciowej idealizacyjnej teorii nauki - Brzechczyn, Krzysztof (My University, 2016)
The aim of this article is to explicate the basic types of comparative methods used in Theda Skocpol’s States and Social Revolution within the conceptual framework of the Idealizational Theory of Science, and to determine the usefulness and place of the comparative methods in the structure of the idealizational theory. In the introduction, I outline a characterization of comparative-historical sociology. Some classifications of comparative analysis are presented in section 1. An analysis of comparative methods used in Skocpol’s theory of revolutions and what methodological discussion it stimulated is outlined in section 2. Section 3 presents the key tenets of the idealizational theory of science and in section 4 the basic types of comparative analysis (parallel, contrast oriented, and macro-causal) are explicated within the conceptual framework of this theory, thus allowing to locate these methods in the idealizational approach to science. In the final section, I consider the status of the theory of revolution developed in historical-comparative sociology in light of the vision of the history of scientific knowledge provided by the idealizational approach to science.
Keywords: idealizacja; metoda porównawcza; teoria rewolucji; Theda Skocpol; socjologia porównawcza; Socjologia historyczna